Global and Chinese growth failure disease burden analysis and projections for adolescents and children, 1990–2021 - Wu, Zhifei; Xu, Runbing; Qiu, DongKai; Wang, Haiyan; Zheng, Jiajing (Frontiers in Public Health, 2025)
ObjectiveThis study aimed to comprehensively analyze the global and Chinese burden of growth failure (GF) in children and adolescents from 1990 to 2021, focusing on mortality, disability-adjusted life years (DALYs), years lived with disability (YLDs), and years of life lost (YLLs). The study also explored disparities across gender, age, socio-demographic index (SDI) regions, and geographic locations to inform targeted interventions.DesignA retrospective analysis was conducted using data from the Global Burden of Disease (GBD) 2021 database. Trends in deaths, DALYs, YLDs, YLLs, and their age-standardized rates (ASRs) were evaluated. Decomposition, health inequality, and prediction analyses were performed to assess contributing factors and future trends.ParticipantsChildren and adolescents aged 0–19 years, with emphasis on those under 5 years, were included in the analysis.ResultsFrom 1990 to 2021, global deaths, DALYs, YLDs, and YLLs for GF declined by 78.17, 77.86, 49.71, and 78.20%, respectively. China exhibited even more pronounced declines (98.16, 98.15, 97.10, and 98.15%). The burden was concentrated in children under 5, with males disproportionately affected. Low-SDI regions, particularly Western Sub-Saharan Africa and South Asia, accounted for over 60% of the global burden, with ASRs up to 1,000 times higher than in high-SDI regions.ConclusionDespite substantial progress, GF remains a critical public health challenge, with pronounced disparities persisting in low-SDI regions. Urgently needed are targeted interventions—particularly for children under 5 in these settings—to address the inequitable burden. These conclusions should be interpreted in light of key limitations: the analysis relies on modeled GBD 2021 estimates that may be biased due to data sparsity and cause-redistribution assumptions in low-SDI contexts; furthermore, incidence/prevalence and intervention coverage were not assessed.